The fungal threat to global food security. Issue 8 (August 2019) - Avery, Simon V.; Singleton, Ian; Magan, Naresh; Goldman, Gustavo H.
Abstract: Fungi threaten the security of food supply to human populations on several fronts. They destroy up to 30 % of crop products through disease and spoilage processes, while mycotoxin-producing fungi and opportunistic pathogens endanger food safety. Control of these fungi is vital for improving food security, but current measures are inadequate and further challenges due to human-population growth and climate change are escalating. Investment and innovation in research on strategies to control fungal growth, harnessed through international, inter-disciplinary collaboration across socio-economic boundaries, provides one key to rising to this challenge.